А.Н.КОНОНОВ ҲӘМ ТЮРКОЛОГИЯ ИЛИМИ - Абдиназимов, Ш.Н. (SCIENCE and SOCIETY, 2023)
This article provides information about the life, work and scientific activities of one of the most famous Turkologists - Andrei Nikolaevich Kononov. His works devoted to Turkic studies, especially Turkic runic monuments, Turkish language, grammar of the Uzbek language are discussed. The special merit of A.N.Kononov in the study of the grammar of the Turkic languages is shown.
Keywords: Turkic runic monuments; Turkology; grammar; Turkic language; Uzbek language; parts of speech; syntax